(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Brucellosis remains one of the most significant zoonotic infections in the world , caused by bacteria of the genus Brucella , especially common in regions with developed agriculture. The chronic form of the disease is a serious medical and socio-economic problem associated with a long course, relapses and multiple complications. This article reviews current data on the factors contributing to the chronicity of brucellosis, including bacterial, immunological and external aspects. The biological properties of the pathogen, features of the immune response, diagnostic and therapeutic aspects, as well as the influence of social and epidemiological factors are analyzed. Particular attention is paid to new approaches to the diagnosis, treatment and prevention of chronic brucellosis, based on the latest research in molecular biology, immunology and pharmacotherapy.